Perlindungan Hukum Hak Cipta terhadap Pembajakan Karya Digital di Indonesia - Risma Fernanda Syafi’iyah; Siti Nur Afifah; Zahwa Sabila Nurul Lailiyah; Selly Salsabila; Mohammad Iqbal; Firza Agung Prakoso (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Digital copyright piracy remains a growing legal issue in Indonesia alongside the rapid development of information technology. This practice not only causes economic losses to creators and copyright holders but also reflects a gap between legal norms and social realities. This study aims to analyze legal protection for digital copyrights and to assess the effectiveness of Law Number 28 of 2014 on Copyright. This research employs a normative legal method using a library research approach by examining statutory regulations and relevant academic literature. The findings indicate that although Indonesia has established an adequate legal framework for copyright protection, its implementation remains ineffective due to low public legal awareness, weak law enforcement, and challenges in monitoring digital platforms. These findings emphasize that effective copyright protection requires not only comprehensive regulations but also synergy between the government, law enforcement authorities, and the development of a strong legal culture within society.